Muscle-Nerve-Nerve Grafting Improves Facial Reanimation in Rats Following Facial Nerve Injury - Charous, Steven J.; Hutz, Michael J.; Bialek, Samantha E.; Schumacher, Jane K.; Foecking, Eileen M. (Frontiers in Neurology, 2021)
Nerve injury resulting in muscle paralysis from trauma or surgery is a major medical problem. Repair of such injuries with existing nerve grafting and reconstructive techniques often results in less than optimal outcomes. After previously demonstrating significant return of function using muscle-nerve-muscle (MNM) grafting in a rat facial nerve model, this study compares a variant of the technique, muscle-nerve-nerve (MNN) neurotization to MNM and interposition (IP) nerve grafting. Thirty male rats were randomized into four groups (1) control with no intervention, (2) repair with IP grafts, (3) MNM grafts and (4) MNN grafts. All groups had the buccal and marginal mandibular branches of the right facial nerve resected. Return of vibrissae movement, orientation, and snout symmetry was measured over 16 weeks. Functional recovery and muscle atrophy were assessed and quantified. All interventions resulted in significant improvement in vibrissae movement and orientation as compared to the control group (p < 0.05). The MNM and MNN groups had significantly less time to forward vibrissae movement as compared to controls (p < 0.05), and a large number of animals in the MNN group had coordinated vibrissae movement at 16 weeks. MNN and IP grafts retained significantly more muscle mass as compared to control (p < 0.05). Thus, MNN grafting is a promising adjuvant or alternative technique for reanimation for patients with unilateral peripheral nerve injury who are not candidates for primary neurorrhaphy.